Influence of autoclave sterilization procedures on the cyclic fatigue resistance of heat-treated nickel-titanium instruments: a systematic review - Emmanuel João Nogueira Leal Silva; Mayara Zanon; Fernanda Hecksher; Felipe Gonçalves Belladonna; Rafaela Andrade de Vasconcelos; Tatiana Kelly da Silva Fidalgo (Restorative Dentistry & Endodontics)
ObjectivesThis systematic review evaluated the influence of autoclave sterilization procedures on the cyclic fatigue resistance of heat-treated nickel-titanium (NiTi) instruments.Materials and MethodsA systematic search without restrictions was conducted in the following electronic databases: PubMed, Scopus, Web of Science, ScienceDirect, Cochrane, and Open Grey. The hand search was also performed in the main endodontic journals. The eligible studies were submitted to the methodological assessment and data extraction.ResultsFrom 203 abstracts, a total of 10 articles matched the eligible criteria. After reading the full articles, 2 were excluded because of the absence of the heat-treated instruments in the experimental design and 3 due to the lack of a control group using heat-treated instruments without autoclave sterilization. From the 5 included studies, 1 presented a low risk of bias, 3 presented moderate and 1 high risk. It was observed heterogeneous findings in the included studies, with autoclave sterilization cycles increasing, decreasing or not affecting the cyclic fatigue life of heat-treated NiTi instruments. However, the retrieved studies evaluating the cyclic fatigue resistance of endodontic instruments presented different protocols and assessing outcomes, this variability makes the findings less comparable within and also between groups and preclude the establishment of an unbiased scientific evidence base.ConclusionsConsidering the little scientific evidence and considerable risk of bias, it is still possible to conclude that autoclave sterilization procedures appear to influence the cyclic fatigue resistance of heat-treated NiTi instruments.